2005
DOI: 10.1183/09031936.05.00095204
|View full text |Cite
|
Sign up to set email alerts
|

Time course of cigarette smoke-induced pulmonary inflammation in mice

Abstract: Inflammation of the airways and lung parenchyma plays a major role in the pathogenesis of chronic obstructive pulmonary disease. In the present study a murine model of tobacco smoke-induced emphysema was used to investigate the time course of airway and pulmonary inflammatory response, with a special emphasis on pulmonary dendritic cell (DC) populations.Groups of mice were exposed to either cigarette smoke or to control air for up to 24 weeks. In response to cigarette smoke, inflammatory cells (i.e. neutrophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
245
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(283 citation statements)
references
References 40 publications
31
245
1
4
Order By: Relevance
“…However, a similar priming mechanism may occur following chronic CS exposure, and this would provide a sufficient explanation for our observation that NK cells in both lungs and spleens exhibit signs of priming. The picture is incomplete (48), but several reports have demonstrated that DC activation occurs in COPD patients and in mouse models (49)(50)(51). Maturation of DCs has been correlated with disease severity, strongly suggesting a mechanistic role for DCs in COPD (49).…”
Section: Discussionmentioning
confidence: 99%
“…However, a similar priming mechanism may occur following chronic CS exposure, and this would provide a sufficient explanation for our observation that NK cells in both lungs and spleens exhibit signs of priming. The picture is incomplete (48), but several reports have demonstrated that DC activation occurs in COPD patients and in mouse models (49)(50)(51). Maturation of DCs has been correlated with disease severity, strongly suggesting a mechanistic role for DCs in COPD (49).…”
Section: Discussionmentioning
confidence: 99%
“…19 Briefly, groups of 10-12 mice were exposed to the tobacco smoke of five cigarettes (Reference Cigarette 3R4F without filter; University of Kentucky, Lexington, KY, USA) four times per day with a 30-min smoke-free interval, 5 days per week for 24 weeks (chronic smoke exposure). An optimal smoke:air ratio of 1:6 was obtained.…”
Section: Cigarette Smoke Exposurementioning
confidence: 99%
“…The chronic inflammatory infiltrate is characterized by augmented numbers of alveolar leukocytes, including both B and T lymphocytes. However, the adaptive immune system may not be essential to the development of pulmonary emphysema in response to chronic tobacco exposure, because emphysema can still be induced in SCID mice, which lack functional lymphocytes (5). This finding indicates that innate inflammatory cells, such as neutrophils and macrophages, may play an essential role in the pathogenesis of COPD.…”
mentioning
confidence: 68%
“…Therefore, we examined whether CSE-and nicotine-induced reductions in neutrophil spontaneous death are a result of blockage of Akt deactivation. Akt is recruited to the plasma membrane through specific binding to PtdIns (3,4,5)P3. Only Akt molecules on the plasma membrane can be phosphorylated and activated by two phosphatidylinositoldependent protein kinases (PDKs), thus Akt phosphorylation has been widely used as an indicator of Akt activation.…”
Section: Cse and Nicotine Block Akt Deactivation And Delay Neutrophilmentioning
confidence: 99%
See 1 more Smart Citation